Eco-cultural approach integrating Islamic values with artha wantilan concept on the fish market design in Kedonganan Bali, Indonesia - Jannah, M; Mutiara, Elok; Kusumadewi, Tarranita (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v10i0.1136, 2019)
Bali is an island that has many coastal areas, one of which is Kedonganan and there is a fish market that is quite famous among the surrounding population and the tourists. This study aims to re-design the Fish Market with an eco-cultural approach. This design approach considers the continuation of nature and also local traditional Balinese Architecture. However, there are several values in Hinduism that contradict the values of the Islamic religion. The values of the Islamic integration argument are used to examine aspects adapted to the artha wantilan concept based on the characteristics of Bale Wantilan so that its application in the design of the fish market still contains elements of Balinese architecture and remains integrated with Islamic values. The used method is descriptive qualitative, by collecting the literature review, examining several aspects related to the object of research, and applying the results of the study in object design. So that the results of this study can know the shape of the roof, building body and foot of the building, and ornaments that are applied and have been adapted to the needs of the fish market building and also integrated Islamic values.